Delivering cognitive behavioural therapy to advanced cancer patients: A qualitative exploration into therapists' experiences within a UK psychological service. (25th March 2018) - Hassan, Suzan; Bennett, Kirsty; Serfaty, Marc
Abstract : Background: Cognitive behavioural therapy (CBT) is commonly used to treat cancer patients with psychological disorders such as depression. There has been little qualitative research exploring the experience of therapists delivering CBT to patients with advanced cancer and long‐term health conditions generally. Therapists' views may help identify difficulties in delivering therapy and how these may be overcome. The aim of this study was to inform practice by qualitatively exploring the experiences of therapists delivering CBT to patients with advanced cancer. Design: Sixteen semi‐structured interviews were conducted with therapists from Increasing Access to Psychological Therapy (IAPT) services in London, UK, who had delivered CBT to patients enrolled on the CanTalk trial. Interviews were recorded, transcribed, and analysed using framework analysis. Results: Therapists reported positive experiences when working with the target population. Flexibility, adaptability, and a consideration of individual needs were identified as important when delivering CBT, but the rigidity of IAPT policies and demand for services were perceived as problematic. Although therapists reported adequate training, specialist supervision was desired when delivering therapy to this complex population. Conclusion: IAPT therapists can deliver CBT to advanced cancer patients, given therapists positive experiences evident in the present study. However, it was concluded that additional service and modifications of therapy may be needed before positive outcomes for both therapists and patients can be achieved.